ENHANCING PUBLIC SPEAKING ABILITY THROUGH FOCUS GROUP DISCUSSION - Tien Yulianti; Ari Sulistyawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this research was to develop a Focus Group Discussion (FGD) model in learning personality development as an effort to improve students' public speaking skills. FGD learning model enables students to possess the ability to think critically, creatively, and innovatively in preparing group presentations and discussions. The results of the implementation of FGD model were expected to be able to develop and enhance students’ public speaking skills, so they have competitiveness in facing of society 5.0. This research was conducted in six steps of development based on the ASSURE model. The development of FGD learning model consisting of presentations and discussions was conducted online and gathering data about audience’s opinion was carried out based on the specified themes. The object of this research was the students who took Personal Development and public speaking courses. The results of data analysis obtained an average score = 8.1 from a maximum score = 10 and a standard deviation = 1.8 which was derived based on 10 components of public speaking skills assessment. The grade was categorized into A (Excellence), B (Good), and E (Failed).